2011 International Conference on Computer Vision 2011
DOI: 10.1109/iccv.2011.6126367
|View full text |Cite
|
Sign up to set email alerts
|

Refractive shape from light field distortion

Abstract: Acquiring transparent, refractive objects is challenging as these kinds of objects can only be observed by analyzing the distortion of reference background patterns. We present a new, single image approach to reconstructing thin transparent surfaces, such as thin solids or surfaces of fluids. Our method is based on observing the distortion of light field background illumination. Light field probes have the potential to encode up to four dimensions in varying colors and intensities: spatial and angular variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 35 publications
(43 reference statements)
0
53
0
Order By: Relevance
“…For example, they propose using Bokode [19], a special pinhole projector, to acquire ray-ray correspondences for directly recovering fluid surface normals. Closest to our approach, Wetzstein et al [29] replace the conventional checkerboard pattern with a LF-probe with 4D spatial and angular coding to obtain more accurate ray-ray correspondences. We study non-linear light paths using ray-ray correspondences.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, they propose using Bokode [19], a special pinhole projector, to acquire ray-ray correspondences for directly recovering fluid surface normals. Closest to our approach, Wetzstein et al [29] replace the conventional checkerboard pattern with a LF-probe with 4D spatial and angular coding to obtain more accurate ray-ray correspondences. We study non-linear light paths using ray-ray correspondences.…”
Section: Related Workmentioning
confidence: 99%
“…The core of our approach is to acquire ray-ray correspondences using the LF-probe [28,29]. A LF-probe, as shown in Fig.…”
Section: Light Field Probe (Lf-probe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al [27] showed that atmospheric turbulence provides a depth cue as larger deflections due to refraction typically correspond to greater depths. Wetzstein et al [29] proposed to recover the shape of a refractive solid object from light field distortions. Alterman et al [2,3] showed that it is possible to locate a moving object through refractive atmospheric turbulence or a water interface.…”
Section: Related Workmentioning
confidence: 99%